Under My Vine - Sleiman, Hucen (2022)
This research is a study of the links that connect habitus, memory, culture to architecture, and the role that plays the latter in constructing and preserving a sense of belonging and identity. The migratory course, from its beginning, through its journey, to the process of resettlements, is used to establish the significant part that the built environment and architecture have in defining who persons are, what they expect, and where they belong. The habitus theory of Pierre Bourdieu is used as the main framework to explain how the predispositions of any individual are culturally and socially constructed. The research argues that the habitus, with memories of places and culture, enter in defining and constructing deep connections with a built environment and its architecture, which start to form a sense of belonging to a particular context. This thesis presents a comprehensive outline to issues related to identity construction, with an emphasis on memory, culture, place, and migration, and the importance of the built environment and architecture in this construction. The ephemeral aspect of identity, which recreates itself constantly, changing and altering its definition, due to external conditions, such as migration, is studied in this research. A significant focus is put on feelings of loss and alienation, also of nostalgia, that result from the process of migration, which is represented as a detachment from the known and familiar context, especially in the process of re-territorialization in new surroundings. This research, through an exploration of the central role that architecture plays in identity construction in the context of migration, maintains that a strong link exists between habitus, memory, culture, and architecture, which is essential in determining individuals’ expectations and their self-image. Finally, the outcome of this research is used to construct a critique of the architectural discipline that fails to be more socially responsive, especially when it comes to questions related to belonging and identity.